The impact of corporate social responsibility directed toward employees on contextual performance in the banking sector: A serial model of perceived organizational support and affective organizational commitment. (11th May 2022) - Bhatti, Sabeen Hussain; Iqbal, Kamran; Santoro, Gabriele; Rizzato, Fabio
Abstract: Using the lenses of stakeholder and social exchange theory, we propose that both perceived organizational support (POS) and affective organizational commitment (AOC) play sequential mediating roles in the relationship between corporate social responsibility (CSR) directed toward employees and organizational citizenship behaviors (OCBs) of employees. The theoretical model was tested using a time lagged data. Further, the information pertaining to the organizational citizenship behaviors of the employees was collected by their immediate supervisors. The mediation hypotheses were tested using process method. Results confirmed a positive and significant relationship between perceived CSR directed toward employees and OCBs, as well as the sequential mediation effect of both POS and AOC between CSR directed toward employees and OCBs. Although the majority of the literature has studied the impact of CSR at the macro level, recently researchers have shifted their focus on the behavioral impact of such activities at the individual level. We particularly focus on CSR directed toward employees and our findings confirm that such CSR activities prove be critical for improving the performance outcomes of the employees.